Selective laser sintering of bonded anisotropic permanent magnets using an in situ alignment fixture. Issue 4 (29th March 2021) - Mapley, Martin Christopher; Tansley, Geoff; Pauls, Jo P.; Gregory, Shaun D.; Busch, Andrew
Abstract : Purpose: Additive manufacturing (AM) techniques have been developed to rapidly produce custom designs from a multitude of materials. Bonded permanent magnets (PMs) have been produced via several AM techniques to allow for rapid manufacture of complex geometries. These magnets, however, tend to suffer from lower residual induction than the industry standard of injection moulding primarily due to the lower packing density of the magnetic particles and secondly due to the feedstock consisting of neodymium-iron-boron (Nd-Fe-B) powder with isotropic magnetic properties. As there is no compaction during most AM processes, increasing the packing density is very difficult and therefore the purpose of this study was to increase the magnetic properties of the PMs without increasing the part density. Design/methodology/approach: Accordingly, this research investigates the use of anisotropic NdFeB feedstock coupled with an in-situ alignment fixture into an AM process known as selective laser sintering (SLS) to increase the magnetic properties of AM magnets. A Helmholtz coil array was added to an SLS machine and used to expose each powder layer during part fabrication to a near-uniform magnetic field of 20.4 mT prior to consolidation by the laser. Findings: Permeagraph measurements of the parts showed that the alignment field introduced residual induction anisotropy of up to 46.4 ± 2.2% when measured in directions parallel and perpendicular to the alignment field. X-ray diffraction measurements also demonstrated a convergence of the orientation of the crystals when the magnets were processed in the presence of the alignment field. Originality/value: A novel active alignment fixture for SLS was introduced and was experimentally shown to induce anisotropy in bonded PMs. Thus demonstrating a new method for the enhancement in energy density of PMs produced via AM methods.